Self-Regulation of Emotion in Students in Yogyakarta Indonesia: Gender Differences - Alhadi, Said; Saputra, Wahyu Nanda Eka; Purwadi, Purwadi; Muyana, Siti; Supriyanto, Agus; Fatmawati, Dwi (Jurnal Kajian Bimbingan dan Konseling, 2019)
The purpose of this study was to identify whether there are differences in self-regulation of emotion skills of male and female students. This study is a comparative study with a sample of 796 students (452 males, 344 females). The sample selection is taken using simple random sampling technique. The instrument used is the scale of self-regulation of emotion. Data analysis used to identify differences in self-regulation of emotion skills of male and female students is independent samples test. The findings of the study indicate that there is a significant difference between the self-regulation of emotion skills of male and female students. This study recommends counseling service to improve self-regulation of emotion skills.